Level of Heavy Metals and Potential Ecological Risks in Irrigated Horticultural Farms in the Vicinity of Lake Ziway, Central Ethiopian Rift Valley Region - GirmaTilahun Yimer (Journal of Toxicology)
Research on heavy metal pollution in horticultural farms located around lakes in the Central Ethiopian Rift Valley Region has focused on measuring the levels of heavy metals and their health implications. However, the ecological risks of horticultural farms contaminated with heavy metals in this region have not been studied. The current study addresses this gap by providing information on the degree of heavy metal contamination and the ecological risk associated with horticultural farms around Lake Ziway, using various pollution indices. An inductively coupled plasma optical emission spectrometer (ICP-OES) was used to measure the concentrations of nine heavy metals (As, Cd, Co, Cu, Cr, Ni, Pb, Hg, and Zn) in a total of 30 composite soil and irrigation water samples, each consisting of a mix of six subsamples. The results indicated that the mean concentrations of Hg, Cd, Pb, and Zn in soils collected from all the sampling sites exceeded the FAO/WHO maximum permissible limit (MPL). The values of both the contamination factor (CF) and contamination degree (Cd) of the heavy metals ranged from 0.04 to 2.66 and 2.81 to 6.14, respectively, indicating a low to medium level of contamination for both indices. The pollution load index (PLI) values of 0.451, 0.449, and 0.157 for sites 2, 1, and 3, respectively, indicate “unpolluted” to “moderately polluted” levels of heavy metal pollution. However, the ecological risk indices (ERIs) at sites 2 and 1 (158.92 and 141, respectively) showed a potentially high ecological risk due to soil pollution. Therefore, close monitoring and early intervention mechanisms must be in place to control pollution in the study area.